Building Capacity in Planning, Monitoring and Evaluation: Lessons from the Field - Horton, Douglas (International Service for National Agricultural Research, 1998)
This paper reports on the author's experiences as manager of a capacity-building project in Latin America. The project aimed to strengthen planning, monitoring and evaluation (PM&E) in agricultural research. Nine lessons are drawn: (1) Project design is much more than a technical process; it is essentially one of negotiation. (2) In capacity-building projects, design activities cannot end when implementation begins. (3) A priority for capacity-building efforts is to prepare managers to deal with complexity, uncertainty and change.(4) In capacity-building efforts, don't patronize managers, but seek to collaborate as equals.(5) Organizational assessment is a complex social process, intertwined with organizational politics. (6) In designing capacity-building projects, it is essential to involve managers and staff members in assessing needs and opportunities. (7) Action-learning strategies offer great potential for capacity building. (8) In the context of strategic management and organizational learning, PM&E take on new meanings. (9) Training is most effective when it is designed to serve a purpose within an organizational change process. Capacity building is more a process of social experimentation than of social engineering. Management systems cannot be imported but need to be developed within organizations. Development agencies should play catalytic, facilitating roles, rather than take responsibility for organizational change. To support genuine capacity development, donors and funding agencies need to ensure that their planning and accountability procedures foster flexibility, innovation, and learning.